Evaluación del PEI, y su incidencia en el trabajo cooperativo de los colegios nocturnos Amazonas y Kleber Franco Cruz de la ciudad de Machala, provincia de El Oro. Periodo lectivo 2011-2012 y propuesta de un modelo de gestión estratégica participativa fundamentado en las teorías del liderazgo e innovación para el buen vivir. - Gordillo Labanda, Jenny Elizabeth (2012)
This research deals with the Institutional Educational Project and its impact on Academic and Administrative Development of the Amazonas and Kleber schools Franco Cruz, El Oro Province, Machala. The general objective was to determine the current situation of the evaluation of the Institutional Educational Project and its impact on cooperative work through study of identity, diagnosis, pedagogical and management proposal, monitoring and improvement project . The present research is structured in three chapters that are summarized below: Chapter I: is related to the problematization that presents very important aspects such as: introduction of research, situation of research, formulation of objectives and the hypothesis approach . The research problem refers to the lack of evaluation of the institutional educational project, which has led to a low level of educational quality and institutional development in the Amazonas and Kleber Franco Cruz night schools in Machala, El Oro province, during The academic period 2011-2012. In addition, reference is made to a theoretical conceptual framework made up of topics that are directly related to each of the variables that include: evaluation, planning, institutional educational project, leadership theory and innovation for good living.